Accuracy of planned versus actual implant positions in mucosa supported guided implant surgery - Ben Yehuda, Daniel. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Posthodontics.; Advisor: Panos Papaspyridakos.; Committee: Hans-Peter Weber, Ali Muftu, and Matthew Finkelman.; Keyword: Dentistry.